Scientific And Theoretical Approaches To Factors Contributing To The Emergence And Development Of Extremism (Eurasian Journal of Humanities and Social Sciences, 2025)
The article highlights views and approaches regarding factors contributing to the emergence and development of extremism, in particular, the results of research in this area by international organizations and scientists.